Effect of classical guidance services on self-confidence of grade XI vocational students - Muhamad Arfan Muharam; Dwi Dasalinda (Himpunan Pengembang Kurikulum Indonesia, 2025)
This study was motivated by the low self-confidence of students in facing academic and social challenges in the school environment. Classical guidance services were chosen as an intervention, as they are considered capable of holistically strengthening students’ psychological aspects. This study aimed to examine the effect of classical guidance services on enhancing students' self-confidence. A quantitative approach was employed using a one-group pretest-posttest design. The participants were 22 eleventh-grade students at SMK Islam Malahayati. The research instrument was a self-confidence questionnaire developed based on Lauster’s five key aspects: self-belief, optimism, objectivity, responsibility, and rational thinking. Data were analyzed using a paired sample t-test to assess pre- and post-treatment differences, with effect sizes calculated using Cohen’s d and Hedges’ g. The findings revealed that classical guidance had a positive impact on increasing students’ self-confidence. Students showed improvement in their belief in self-ability, optimistic attitudes, objective self-assessment, a sense of responsibility, and rational decision-making. These results were supported by statistical analysis and aligned with findings from previous studies. Therefore, classical guidance proved to be an effective approach for fostering positive attitudes and preparing students to face future challenges. Abstrak Penelitian ini dilatarbelakangi oleh rendahnya kepercayaan diri peserta didik dalam menghadapi tantangan akademik dan sosial di lingkungan sekolah. Layanan bimbingan klasikal dipilih sebagai intervensi untuk mengatasi permasalahan tersebut karena diyakini mampu memperkuat aspek-aspek psikologis peserta didik secara menyeluruh. Penelitian ini bertujuan untuk mengetahui pengaruh layanan bimbingan klasikal terhadap peningkatan kepercayaan diri peserta didik. Penelitian ini menggunakan pendekatan kuantitatif dengan desain one group pretest-posttest. Subjek penelitian adalah peserta didik kelas XI di SMK Islam Malahayati yang berjumlah 22 orang. Instrumen yang digunakan berupa angket kepercayaan diri yang dikembangkan berdasarkan lima aspek utama menurut teori Lauster, yaitu keyakinan diri, sikap optimis, objektivitas, tanggung jawab, dan kemampuan berpikir rasional. Data dianalisis menggunakan paired sample t-test untuk mengetahui perbedaan sebelum dan sesudah layanan, serta dihitung ukuran efeknya menggunakan Cohen’s d dan Hedges’ g. Temuan penelitian menunjukkan bahwa layanan bimbingan klasikal memberikan pengaruh positif terhadap peningkatan kepercayaan diri peserta didik. Peserta didik menunjukkan perkembangan dalam aspek keyakinan diri, sikap optimis, objektivitas dalam menilai diri, kemampuan bertanggung jawab, dan berpikir rasional. Hasil ini diperkuat dengan data statistik dan pembandingan dengan hasil penelitian sebelumnya yang sejalan. Layanan bimbingan klasikal terbukti menjadi pendekatan yang efektif dalam membentuk sikap positif dan kesiapan peserta didik dalam menghadapi tantangan masa depan. Kata Kunci: bimbingan klasikal; kepercayaan diri; layanan bimbingan; pembentukan karakter; peserta didik